UNWE Internationalisation: Successes and Challenges - Stefanova, Albena (Research Papers, 2024)
The article presents a project on the internationalisation of a Bulgarian economic university within the context of the pandemic, educational trends and policies, as well as a strive for global recognition in the spheres of academic and research activity. It makes an overview of the concept of internationalisation in higher education and the approaches and strategies to internationalisation developed and implemented by higher education institutions and educational experts. The in-depth research is expected to provide the basis for the updating and optimisation of the internationalisation strategy of the University of National and World Economy for the period 2020 – 2025.
Keywords: Higher education; Internationalisation; Internationalisation of higher education